Estrogen receptor β gene polymorphisms are associated with higher bone mineral density in premenopausal, but not postmenopausal southern Chinese women - Lau, H.H.L; Ho, A.Y.Y; Luk, K.D.K; Kung, A.W.C (Bone (New York, N.Y.), 2002)
Bone mineral density (BMD), the main determining risk factor for osteoporotic fractures, has a strong genetic component. Estrogen and its receptors play a critical role in both skeletal maturity and bone loss. We investigated the association between dinucleotide (cytosine-adenine; CA) repeat polymorphisms located in the flanking region of the estrogen receptor β gene and bone mineral density (BMD) in 325 healthy southern Chinese women. BMD at the lumbar spine and hip region were measured using dual-energy X-ray absorptiometry (DEXA). The number of the repeats observed in our population ranged from 16 to 28. After adjusting for age, height, weight, and years of estrogen exposure, we observed that premenopausal subjects (n = 120) bearing at least one allele of 20 CA repeats had significantly higher BMD at the L2–4 lumbar spine (1.049 ± 0.016 vs. 0.984 ± 0.015; p = 0.01), total hip (0.836 ± 0.014 vs. 0.813 ± 0.013; p < 0.02), femoral neck (0.773 ± 0.014 vs. 0.728 ± 0.013; p = 0.02), trochanter (0.665 ± 0.013 vs. 0.614 ± 0.012; p = 0.01), and Ward’s triangle (0.715 ± 0.017 vs. 0.651 ± 0.016; p = 0.02). There was no difference in the vertebral area of L-3 and femoral neck width in these premenopausal women with or without 20 CA repeats. However, in postmenopausal women (n = 205), Estrogen receptor β (ERβ) gene polymorphisms were not related to BMD at any skeletal site. We conclude that ERβ gene polymorphisms are associated with higher BMD in premenopausal women, suggesting that the ERβ gene may have a modulatory role in bone metabolism in young adulthood.